Oral Presentations Abstracts: THE ITALIAN MASTER IN CLINICAL BIOETHICS CONSULTATION: 2013-2020 EXPERIENCE - SACCHINI, Dario; REFOLO, Pietro; CORSANO, Barbara; PICOZZI, Mario; PEGORARO, Renzo; IANNONE, Maria Teresa; TAMBONE, Vittoradolfo; DEI TOS, Gian Antonio; BUCCELLI, Claudio; SPAGNOLO, Antonio G. (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
View of Volume 66, Special Issue, September 2021 This work is aimed at critically illustring the eight-year experience of the Master in “Clinical Bioethics Consultation” (2013-2020). This advanced second-level Master was promoted in 2013 by the Catholic University of the Sacred Heart of Rome, and co-worked by other Italian clinical as well as academic institutions (University Campus Bio-medico of Rome, Insubria University of Varese, “Federico II” University of Naples, Lanza Foundation of Padua, Local Health and Social Care Unit n. 7 (ULSS) of Veneto Region, Treviso; Ospedale San Giovanni Calibita Fatebenefratelli – Isola Tiberina, Rome, and Italian Group for clinical ethics consultation (GIBCE)). To this aim, it first will discuss two points: on the one hand, an epistemological one, i.e. the justification of the activity of ethics consultant in clinical settings supported by the authors; on the other hand, a pedagogical one, i.e. the identification of the learning needs clinical bioethics gives birth to. The second part of the work will focus on the experience of the Master, explaining its basic features (objectives, methods, contents, evaluation tools, etc), offering a critical review, and identifying the challenges this initiative has to face in the next future.